Human Monkeypox Experience in a Tertiary Level Hospital in Milan, Italy, between May and October 2022: Epidemiological Features and Clinical Characteristics - Candela, Caterina; Raccagni, Angelo Roberto; Bruzzesi, Elena; Bertoni, Costanza; Rizzo, Alberto; Gagliardi, Gloria; Canetti, Diana; Gianotti, Nicola; Mileto, Davide; Gismondo, Maria Rita; Castagna, Antonella; Nozza, Silvia (Viruses, 2023)
Background: Monkeypox virus (mpxv) started to spread to Europe and North America at the beginning of the current outbreak in May 2022, and the World Health Organization (WHO) declared Human Monkeypox (mpox) as a public health emergency of international concern (PHEIC) in July 2022. The aim of this observational analysis is to describe demographical data, symptoms presentation and clinical course till outcome of individuals diagnosed with mpox, between May and October 2022, at our open-access Sexual Health Clinic in IRCCS San Raffaele Hospital in Milan, Italy. Methods: Among people who accessed our Sexual Health Clinic, we considered, as suspected diagnosis of mpox, individuals with consistent symptoms and epidemiological criteria. Following the physical examination, oropharyngeal, anal, genital and cutaneous swabs, plus plasma, urine and seminal fluid were collected as biological materials to detect mpxv DNA. We also performed a screening for sexually transmitted infections (STIs). Results: Overall, 140 individuals with mpox were included in this study. Median age was 37 (interquartile, IQR 33, 43) years old. Males were 137 (98%) and men who have sex with men (MSM) were 134 (96%). As risk factors, we detected travels abroad in 35 (25%) individuals and close contact with mpox cases in 49 (35%). There were 66 (47%) people living with HIV (PLWH). Most frequent symptoms were fever (59%), lymphadenopathy (57%), cutaneous (77%), genital (42%), anal (34%) and oral (26%) lesions, proctitis (39%), sore throat (22%) and generalized rash (5%). At mpox diagnosis, we also observed N. gonorrhoeae in 18 (13%) cases, syphilis in 14 (10%) and C. trachomatis in 12 (9%). Two (1%) people received a concomitant diagnosis of HIV infection. We attended to 21 (15%) complications, with nine (6%) cases of hospitalization including six (IQR 3,7) median hospital days. Forty-five (32%) patients were treated with non-steroidal anti-inflammatory drugs (NSAIDs), 37 (26%) with antibiotics and eight (6%) with antiviral drugs. Conclusions: Similarly to other international cohorts, sexual transmission was most frequently present, and concomitant STIs were common. Symptoms were heterogenous, self-resolving and responsive to therapy. Hospitalization was necessary in few patients. There is uncertainty about the future development of mpox and further studies (e.g., potential disease reservoirs, other possible means of transmission, predictors of severe disease) are still needed.